RENDAHNYA MINAT DALAM MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI (Studi Kasus Di Dusun Bontocinde Kabupaten Gowa) - Putri, Indah; Ahmad, M. Ridwan Said (Citra Media Publishing, 2024)
The research was intended to analyse the causes of students' low interest in continuing their studies to higher education. The method used in this research is qualitative method. The subjects of this study were high school students in Bontocinde village. Data were collected through interviews, observation and documentation. Data analysis in this study includes data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that the causes of students not continuing their education to college in Bontocinde village, Gowa Regency are caused by several factors, namely: first, family economic limitations, second, the inability of the brain to continue education, third, there is no support from parents, fourth, there is no desire to continue education and prefer to work.